Pest and Disease in the Gayo Coffee Agroforestry System, Central Aceh - Elis Nina Herliyana; Fifit Kultsum; Adisti Permata Sari Putri Hartoyo (Institut Pertanian Bogor, 2026)
The agroforestry system is a land management approach that considers social, economic, and environmental factors. Gayo coffee (Coffea arabica) is the primary commodity for the residents of Mude Nosar Village in Central Aceh, where the agroforestry technique is applied. However, pest and disease attacks on coffee plants reduce productivity. Pest and disease identification research has yet to be completed. The purpose of this study was to identify the different types of pests and diseases to determine the attack intensity and control potential in the Gayo coffee agroforestry system. Purposive sampling, vegetation analysis, and pest and disease attack calculation were the methods used. The Forest Pathology Laboratory detected symptoms of the attack by examining the fungus’ macroscopic and microscopic structure. The pests discovered included fleas (Heteropsylla cubana) and caterpillars (Hyposidra talaca). The diseases discovered were anthracnose and leaf rust. The intensity of fleas, anthracnose, and leaf rust attacks was less than 30% each. Using coffee skin waste, livestock manure, and natural enemies, may control pests and conditions in the Gayo coffee agroforestry system while also implementing organic agroforestry management. Natural enemies include Trichoderma harzianum, weaver ants (Oecophylla smaragdina), and spiders (Araneae) are suggested. Keywords: agroforestry, Central Aceh, disease, Gayo coffee, pest